Improving Maternal Health Through Pregnant Women’s Nutrition Education in Pregnancy Women’s Classes - Juwariah, Titik; Santoso, Edi; Wahyuningsih, Diyan; Jaroh, Assolychatu (STIKes Patria Husada Blitar, 2024)
Lack of nutrition in pregnant women can cause abortion, low birth weight (LBW), premature birth, or even stillbirth during labor. Low levels of knowledge cause mothers to not understand how to fulfill the nutritional needs of pregnant women during their pregnancy. This activity aimed to increase pregnant women's knowledge of nutrition during pregnancy. The population was 10 pregnant women in the Pregnant Women's class in Kedungbanteng village. The method of the activity was to provide education through counseling, providing leaflets, and conducting pretest and posttest evaluations. The activity was carried out on Saturday, March 22, 2024, by a service team from Stikes Ganesha Husada Kediri. The results of the study showed that education for pregnant women increased knowledge about: Healthy eating patterns for pregnant women, benefits of healthy eating patterns for pregnant women, problems related to eating patterns for pregnant women, nutritional needs for pregnant women, signs and symptoms of malnutrition in pregnant women and the impact of nutritional status on the labor process. The result showed that before education, the number of pregnant women who had good knowledge was 3 people (30%), sufficient knowledge was 2 people (20%), and poor knowledge was 5 people (50%). After the intervention, the number of pregnant women who had good knowledge was 8 people (80%), sufficient knowledge was 1 person (10%) and poor knowledge was 1 person (10%). This revealed that education through pregnancy classes needs to be carried out and evaluated routinely by the midwife in charge, so that pregnant women have broad knowledge and insight and can make the right decisions in preparing for childbirth and the baby will be born healthy and safe as well as the mother healthy and safe without complications. The cadre mother should patiently provide assistance during pregnancy and childbirth.